THE IMPROVEMENT IN A DONUTS PRODUCTION LINE - Campos, Franciele Marcela de; Reis Filho, Ramilio Ramalho (Revista Interface Tecnológica, 2020)
Performance Indicators are essential tools that help managers when managing their organizations, allowing companies to make decisions that optimize their processes, improve their quality and increase productivity. The objective of this work is, through Performance Indicators, to identify where it is necessary to apply an improvement in a donut production line, of the company “Donuts Ana”, which is located in the city of Américo Brasiliense, in the state of São Paulo. The methods used were: bibliographic research and case study, with application of observations of the production processes. It can be concluded that, after the case study, it was possible to identify that the application of the improvement would be in the "Prepare Dough" stage. In addition to identifying where improvement was needed, through the case study it was indicated which improvement to apply. The indication of improvement was, then, to decrease the time of water in the fire by 15 seconds. The company applied the improvement to the process, obtaining a 20-minute reduction result in the “Prepare the Dough” step, that is, there was a reduction from 46 to 26 minutes of preparation.
Keywords: Performance Indicators; Donuts; Processes